Serologic Evidence of Pertussis Infection in Vaccinated Iranian Children - Anahita Sanaei Dashti; Abdollah Karimi; Reza Arjmand; Mohsen Moghadami; Taherh Kheirkhah; Farideh Shiva; Zari Gholinejad; Hassan Joulaei (Iranian Journal of Medical Sciences, 2012)
Background: It seems that the incidence of pertussis-like illnesses is considerably increasing despite the wide coverage of immunization with the whole cell pertussis vaccine. We aimed to investigate the occurrence of pertussis in vaccinated children by measuring anti-pertussis antibodies. Methods: In this cross-sectional study, blood samples were taken from vaccinated children aged 2, 4, 6, 12, 18, and 72 months. Anti-pertussis IgG and IgA were measured by ELISA. P<0.05 was considered significant.Results: 725 children were enrolled in the study. Geometric mean titers for IgG that showed a slight decease after 2 months of age and increased distinctly in children aged 72 months. The frequency of the individuals whose IgG was above the determined cut-off (derived from mean+2SD) was observed in 1% of the 2, 4, and 6-month-old infants, 6% of the 12 and 18-month-olds and 12% of the 6-year -old children. Positive IgA titers were detected in 5, 9, 6, 23, 11, and 8% of children aged 2, 4, 6, 12, 18, and 72 months, respectively.Conclusion: Since a considerable percentage of children had high levels of anti-pertussis IgG antibodies (≥2 SD), positive anti-pertussis IgA, and most importantly an increased level of anti-pertussis IgG geometric mean titer at 6 years of age, further investigations regarding the protection provided by the presently used pertussis vaccine seems necessary.